Education On Recycling Paper Waste Into Seed Paper As An Environmentally Friendly Product For Vocational School Students - Yoesti Arianti; Rosita Dewati (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
Paper is a material with various daily applications, as a medium for writing, printing, drawing, wrapping, etc. Although in the digital era the role of paper is increasingly minimal, it cannot be denied that the use of paper continues. Besides being useful, paper also leaves a problematic side when it becomes waste. Paper waste that is tried to be eliminated by burning will cause air pollution in the form of disturbing and dangerous smelling smoke, especially in large and continuous volumes. Recycling paper waste is important in order to prevent and minimize environmental damage due to inappropriate handling. The process of recycling paper aims to process paper waste into "new" paper that can be reused and has a selling value. By utilizing household equipment that is generally available at home, this training activity is carried out through simple traditional methods, namely soaking, blending, to the process of filtering paper pulp and drying. The training was carried out on 45 students of SMK N 1 Trucuk, Klaten. This training produces practical solutions for dealing with paper waste while providing basic provisions for students to be able to recycle used paper, so that the implementation of creativity in the future is useful. With the uniqueness of the visuals of paper that is made artistically, it can also be applied as a material in making handicraft products that have sales value.